Familial multiple basal cell carcinoma (Gorlin's syndrome): A case report of a father and son - Balkrishna Nikam; Ashok Kshirsagar; Pratik Shivhare; Amitoj Garg (Wolters Kluwer Medknow Publications, 2013)
Gorlin syndrome is a rare familial disorder characterized by numerous basal cell carcinomas along with facial and skeletal findings. Here, we report a father and son case, presented with features of Gorlin syndrome.